Getting Treatment and Care Services Right for Children and Adolescents to Reach High Viral Suppression. (15th August 2018) - Penazzato, Martina; Sugandhi, Nandita; Essajee, Shaffiq; Doherty, Meg; Ficht, Allison; Phelps, Benjamin Ryan
Abstract : Abstract: In August 2014, PEPFAR and the Children's Investment Fund Foundation launched the Accelerating Children's HIV/AIDS Treatment (ACT) initiative with the aim of doubling the number of children on antiretroviral treatment in 9 African countries. Increasing rates of pretreatment drug resistance and use of suboptimal treatment regimens and formulations result in poor adherence and high rates of viral failure. Supporting adherence and ensuring appropriate treatment monitoring are needed to maximize duration of first-line treatment and enable timely sequencing to subsequent lines of antiretroviral treatment. Although timely antiretroviral treatment is the core of clinical care for infants, children and adolescents living with HIV, ensuring a broader package of biomedical and non-biomedical interventions is also required to address highly prevalent comorbidities among children living with HIV. Providing such a comprehensive package has been challenging for health care workers who lack the necessary skills and confidence to care for pediatric populations. Efforts to simplify clinical management and specific training and mentorship are needed to address these challenges. In this article, we review the progress made during the ACT initiative and the persistent challenges in achieving and maintaining virological suppression across the age spectrum. We identify innovations needed to build on the success of the ACT initiative. Despite the challenges, achieving high levels of virological suppression in children and adolescents is possible. The complexity of pediatric HIV treatment can be offset as antiretroviral regimens become more effective, tolerable, and easier to prescribe and administer. Meanwhile, basic programmatic elements to address comorbidities as well as support health care workers remain critical. In this article we review the progress made through the ACT initiative, as well as identify innovations needed to address persistent challenges to viral suppression across the age spectrum.